Prognostic value of lymph node ratio and extramural vascular invasion on survival for patients undergoing curative colon cancer resection - Parnaby, C N (Br J Cancer, 2015)
BACKGROUND: Increasing lymph node ratio (LNR) (ratio of metastatic lymph nodes to the total number of harvested lymph nodes) and extramural vascular invasion (EMVI) have been proposed as adverse prognostic indicators in colorectal cancer, although their use remains variable and controversial. The aim of the present study was to assess the prognostic value of LNR and EMVI in predicting survival for patients undergoing curative colon cancer resection. METHODS: Between 2006 and 2012, 922 patients underwent curative colon cancer resection. Surgical technique and pathological assessment did not change during the study period. Clinical and pathological data were collected from a prospectively maintained database. The primary outcome measure was overall survival and disease-free survival. LNR was separated into five categories based on three previously calculated cutoff values: LNR 0 (no lymph nodes involved), LNR 1 (ratio 0.01<0.17), LNR 2 (ratio 0.18–0.41), LNR 3 (ratio 0.42–0.69), and LNR 4 (ratio >0.70). RESULTS: Nine hundred and twenty-two patients underwent colon cancer resection. The median follow-up for survivors was 52.8 months (IQR 34.6–77.6). The median total number of lymph nodes harvested was 16 (IQR13-22). On multivariate analysis, both pN and LNR were strongly associated with overall and disease-free survival. Using the Akaike information criterion (AIC), LNR had greater prognostic value compared with pN. For overall survival, compared with patients in LNR category 0, hazard ratios (95% CI) for those in categories 1, 2, 3 and 4 were 1.37 (1.03,1.82), 2.37 (1.70,3.30), 2.40 (1.57,3.65) and 5.51 (3.16,9.58), respectively. For disease-free survival, patients had hazard ratios (95% CI) of 1.78 (1.25,2.52), 3.79 (2.56,5.61), 2.60 (1.50,4.48) and 4.76 (2.21,10.27), respectively. The presence of EMVI was a significant predictor of decreased overall and disease-free survival (P<0.001). CONCLUSIONS: This study demonstrated, in the presence of high surgical, oncology and pathological standards, EMVI and increasing LNR were independent predictors of decreased overall and disease-free survival for patients undergoing curative colon cancer resection. LNR was superior to pN stage in predicting overall and disease-free survival.